PENURUNAN KADAR ION LOGAM TEMBAGA (CU) PADA LIMBAH CAIR INDUSTRI ELEKTROPLATING MENGGUNAKAN METODE ELEKTRODEPOSISI - Tangke Veronika; Bohari Yusuf; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2018)
The reduction of copper concentration in the electroplating industry wastewater by electrodeposition method by means of Atomic Absorption Spectrophotometer (AAS). The result of research showed that degradation and is big of elimination percent of copper metal have with the effect of time contact and voltage at optimum hence in getting results of final concentration of iron (Fe) successive plate 4,02 ppm and 2,84 ppm of concentration early 35,86 ppm and elimination percent of exclusion at optimum parameter in getting result successive 88,403 % and 92,069 %. While the results of the final concentration of Aluminium (Al) successive plate 2,38 ppm dan 2,22 ppm of concentration early 35,86 ppm and elimination percent of exclusion at optimum parameter in getting result successive 93,363 % dan 93,814%.